Effect of betaine and selenium on the growth and photosynthetic pigment production in Dunaliella salina as biostimulants. Issue 21 (3rd January 2020) - Constantinescu-Aruxandei, Diana; Vlaicu, Alexandru; Marinaș, Ioana Cristina; Vintilă, Alin Cristian Nicolae; Dimitriu, Luminița; Oancea, Florin
ABSTRACT: The aim of our study was to establish the effect of selenium and betaine on the growth of D. salina, accumulation of photosynthetic pigments and antioxidant activity of the hydrophobic fraction. This approach was an attempt to demonstrate 'microalgae biostimulant' effects, similar to 'plant biostimulant' effects, i.e. increased tolerance to abiotic stress and enhanced accumulation of bioactive compounds. A high-throughput assay was done in 24-well microplates, at 15% NaCl and different concentrations of sodium selenite (0, 0.5, 2 and 8 µM) or betaine (0, 5, 50 and 500 µM). Both selenium and betaine induced a slight delay in algae growth during the actively growing stage but the final density reached similar values to the control. Betaine significantly enhanced (50%–100%) carotenoids and chlorophyll a accumulation, in a concentration depending manner. Antioxidant activity increased almost 3-fold in extracts of algae treated with 50 µM betaine. Selenium had a much more discrete effect than betaine on pigments biosynthesis. The antioxidant activity of the extracts increased 2-fold in the presence of Se compared to the control. Our work proves that it is possible to enhance production and activity of bioactive compounds from microalgae by using ingredients, which already proved to act as plant biostimulants. Abstract : Exogenous betaine and selenium salt enhance accumulation of carotenoids on halotolerant microalgae grown in high light and salinity stress